Palazzo Querini Stampalia, Konceptmodell - (:unkn) unknown (Chalmers tekniska högskola // Institutionen för arkitektur och samhällsbyggnadsteknik, 2022)
Carlo Scarpa is the architect behind the modern renovation of the garden and part of the ground floor for the Venetian institution Querini Stampalia. Scarpa is admired for his balanced combination of old and new elements, as well as on a great workmanship of the materials. This model represents the concept of the building. The purpose being to capture the feeling of the building, of the materials, elements and of how Scarpa is allowing the water to take its place. The model is made from concrete, a material widely used in the renovation of Palazzo Querini Stampalia. The two elements placed in the pool of water represent two objects found important and significant, the first one being the staircase leading down to the water and the second one being an abstract version of the iron gates.
Palazzo Querini Stampalia model